Third Molar Development Reliability for Radiographic Age Estimation (Demirjian's Method) - Marvi Shaikh, Syeda Sadia Hassan, Sana Shah, Neelam Memon, Alvina Ali Shaikh, Hassan Shahid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The determination of age after a person has died is a potential stage in the postmortem profiling process that leads to definitive identification. Demirjian's method, designed for use with children, establishes maturity scores as a function of age using eight developmental stages and polynomial functions to estimate age as a function of the score. Aim: This study's purpose was to examine the accuracy of age estimate by employing Demirjian's eight teeth approach following French maturity scores & an Indian-specific formula generated from third molar growth phases by use of orthopantomograms. Materials and Methods: 30 participants, each with a known chronological age and gender, had dental panoramic tomograms taken, which were then assessed using Demirjian's standards. The Indian method and the Demirjian formula were used to calculate ages. The P values obtained from the statistical analysis, which included the Chi-square test and the ANOVA test, were statistically significant. Results: Both Indian and Demirjian's formulations had an average underestimate of age. Since the Indian method had a reduced mean absolute error, it may be used to estimate ages Additionally, females complete dental development sooner than boys do since they were faster to reach dental maturity. Conclusion: If population-specific formulae are developed using regression analysis and ethnic and environmental variance is taken into account, more accuracy may be attained.